Effects of Company Size, Profitability and Auditor's Reputation on Audit Delay And its Impact on Abnormal Return - Kevin Phillips; Sutandi Sutandi (Komunitas Dosen Indonesia, 2022)
The purpose of this research is to study the effect of firm size, profitability, auditor's reputation for delays in audit completion and its effect on abnormal returns in companies listed on the LQ45 Index. Secondary data for 2017-2019 from 25 companies used in this study were selected using a purposive sampling method according to research needs by selecting companies as samples. The technique of analyzing data in this study uses two regressions, namely multiple linear regression and standard linear regression which is processed using SPSS version 25. This study gives the results that company size (X1) and profitability (X2) partially have a negative and significant influence on delays. completion of the audit, while the reputation of the auditor (X3) in a partial way does not affect the delay in the completion of the audit (AD). Simultaneously, the three independent variables have a significant effect on the delay in audit completion. This study also provides results that the delay in audit completion has no effect on abnormal returns (Y) on LQ45 index companies in 2017-2019